Pressure Ulcers: Risk Factors, Prevention and Surgical Management - Mohd Altaf Mir; Prince Kumar; Rajesh Maurya; Jaya Jain; Sakshita Pal; Beena Kumari (New Advances in Medicine and Medical Science Vol. 2, 2023)
This chapter provides an evidence-based approach to the prevention and management of pressure ulcers, a common healthcare challenge that can lead to serious complications for patients. The chapter reviews the causes and risk factors of pressure ulcers and emphasizes the importance of early identification and prevention. The chapter also discusses the latest research and best practices for the management of pressure ulcers, including wound assessment and treatment, pain management, and infection prevention. In addition, the chapter highlights the role of interdisciplinary collaboration and patient-centered care in the prevention and management of pressure ulcers. The contributions of this chapter lie in providing healthcare professionals with practical recommendations and strategies for improving patient outcomes and reducing the burden of pressure ulcers on healthcare systems.